Dimethoate Induced Behavioural Changes in Juveniles of Cyprinus carpio var. communis under Temperate Conditions of Kashmir, India - Imtiyaz Qayoom (The Scientific World Journal, 2016)
The present study was designed to investigate acute toxicity of dimethoate on juvenile Cyprinus carpio var. communis. Fishes weighing 10±2 gms were selected and mortality data was statistically evaluated by Finney’s Probit Method. The 96-hour LC50 value for Cyprinus carpio was found as 1.1 ppm in static bioassay system. Mean values of physicochemical parameters of aquarium waters determined during bioassay depicted slight variation indicating that the mortality in aquarium fishes occurred due to pesticide exposure and not suffocation. Lab. temperature ranged from 12 to 13°C; water temperature ranged from 11 to 12°C; dissolved oxygen ranged from 3.90 to 4.56 mg/L; pH ranged from 6.90 to 7.05; total dissolved solids ranged from 2.66 to 3.0 × 103 mg/L, while CO2 remained at a constant value of 2.0 mg/L. The fishes elicited various behavioural responses such as uncoordinated movements, convulsions, excessive mucus secretion, and imbalanced swimming which ended in a collapse to the bottom of the aquarium. Prior to death, the clinical signs like scale erosion, pale body colour, and hemorrhagic patches over the body were noticed which became more vivid up to the termination of experiments. Results of the study indicate potential toxicity of dimethoate in fingerlings of common carp for which the natural waterbodies must be continuously monitored to reduce its impact across food chains.